CONTROL SMARTHOME DISTANCE CONTROL BASED FUZZY LOGIC - Despaleri Perangin-Angin; Gusman Jaya Ndruru; Thomson Purba; Amos Marulitua Butar Butar (INFOKUM, 2021)
SmartHome (smart home) is a part of IoT where all everyday objects or furniture that are familiar with people's lives are “smarted” due to the integration of technology in the form of a versatile microcontroller. In terms of Smart Home, IoT will be present in the form of items that are often found in ordinary people's homes. This research was conducted to develop a system that can assist in performing operations on electronic equipment used daily at home with a smartphone as its control. This research includes the stages of the prototype and system development method that will be developed using the Arduino Uno ATMEGA328 microcontroller hardware, NodeMCU (ESP8266), Bluetooth as the main control system connected to the internet network using a wireless router and as software for control of the system designed using Android-based application, namely the MIT Application Inventor open source application. In conducting experiments to show that this control system is able to work properly as expected so that users can turn off and on electronic devices such as lights, fans and others.